Pride and prejudice: exploring how identity processes shape public attitudes towards Australian counter-terrorism measures - Williamson, Harley (The Australian and New Zealand journal of criminology, 2019)
Counter-terrorism measures are often described as pre-emptive, punitive, and afford authorities exclusive and expanded powers. Yet they continue to attract public support. Why is this the case? A consistent finding in traditional crime control research shows a link between perceived threat from racial or ethnic minority groups and their perceived involvement in crime. This perceived relationship results in public support for punitive crime control measures for such groups. Similar connections can be made between terrorism and Muslims. It is thus possible that perceiving Muslims to be threatening may help explain enhanced public support towards harsh counter-terrorism measures. This study draws on survey data of a national sample Australian residents (N = 1199) to test this hypothesis. Findings show the importance of both identity processes and perceptions of Muslims as threatening in shaping support for punitive counter-terrorism strategies. Results also demonstrate how social identity can moderate the effect of perceived threat on support for such strategies. Theoretical and policy implications of this study are outlined.